The empowered project manager: Employee perception of empowerment - Katharina Goerz (Journal of Applied Leadership and Management, 2021)
Research question: What factors of empowerment are required from the project manager's perspective? Methods: Interviews with 17 project managers at a multi-national technology organisation were conducted, as well as a survey to explore their current empowerment status. Both existing factors in empowerment literature (deductive) and possible additional factors (inductive) were analysed. Results: The major findings of this study's qualitative analysis are that the factors of socio-structural empowerment, access to opportunity, formal power sources, informal power sources, information, support, and resources, were confirmed as required empowerment factors for project managers. Also, three of the four factors of psychological empowerment - competence, self-determination, and impact - are confirmed as required factors. However, the factor meaningfulness needs to be further investigated regarding its effect on project manager empowerment. Further identified factors are role ambiguity, collaborative project team culture, and intrinsic motivational factors: affiliation, acknowledgment, growth, and achievement motivation. A deeper understanding of the required factors of empowerment from the project manager's perspective is developed. Furthermore, the quantitative analysis revealed that project managers currently have a below-average level of socio-structural and psychological empowerment, except for the factors access to support, meaningfulness, and competence.
Keywords: 650